Biomimic Oxidation of Pyridoxine by Peroxo Complex: A Kinetic and Mechanistic Study - Sekar, A.; Peter Pascal Regis, A. (Asian Journal of Chemistry, 2010)
Bis-(ethylene diamine),bis-(diethylene triamine)peroxo dicobalt(III) perchlorate complex is synthesized by solution route. The prepared m-peroxo complex is characterized by FT-IR and electronic spectroscopy. The biomimic kinetics oxidations of pyridoxine by peroxo complex have been studied in aqueous medium. The reaction is first order each in the concentration of peroxo complex and H+ concen-tration. Increase in ionic strength has no effect on the reaction rate. The reaction does not induce the polymerization of acryl amide. The main products of the reaction has been isolated and identified by the spot test. The Arrhenius and the thermodynamic parameters have been calculated from the effect of temperature on the reaction rate. A suitable mechanism has been proposed and the experimental result is derived.